2020
DOI: 10.1111/jnp.12207
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of affective theory of mind ability and its relation to neuropsychological functions in Alzheimer's disease

Abstract: Although cognitive theory of mind (ToM) has been largely studied within neurodegenerative disorders including Alzheimer's disease (AD), studies focusing on affective ToM are relatively limited, yielding inconsistent findings. The current study aimed at investigating affective ToM abilities within different stages of AD (mild AD dementia [ADD], mild cognitive impairment [MCI], and subjective cognitive impairment [SCI]), together with its relationship with neuropsychological functioning. Eighty‐one participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 75 publications
1
18
0
Order By: Relevance
“…We are now, involuntarily, preforming a quasi live version of the “Reading the mind in the eyes” test on a daily basis. Studies using the traditional version of the test [ 1 ] (in "pre-Coronavirus" research) showed that patients with Alzheimer's dementia are impaired in this test [ 2 ] as are patients with schizophrenia [ 3 ], autism spectrum [ 3 ] or somatoform disorders [ 4 ], while patients with borderline personality disorder actually outperform controls [ 5 ]. Two clusters have been found in bipolar disorder and major depressive disorder with the majority of patients performing similarly to healthy controls [ 6 , 7 ].…”
mentioning
confidence: 99%
“…We are now, involuntarily, preforming a quasi live version of the “Reading the mind in the eyes” test on a daily basis. Studies using the traditional version of the test [ 1 ] (in "pre-Coronavirus" research) showed that patients with Alzheimer's dementia are impaired in this test [ 2 ] as are patients with schizophrenia [ 3 ], autism spectrum [ 3 ] or somatoform disorders [ 4 ], while patients with borderline personality disorder actually outperform controls [ 5 ]. Two clusters have been found in bipolar disorder and major depressive disorder with the majority of patients performing similarly to healthy controls [ 6 , 7 ].…”
mentioning
confidence: 99%
“…It has been consistently reported in more recent meta-analysis study [ 11 ]. The correlation between neurocognitive function and RMET was also observed in recent studies involving various clinically-ill patients groups, such as Autism spectrum disorder [ 11 ], Attention deficit hyperactivity disorder [ 21 ], and dementia [ 22 ]. Reasoning by analogy is the ability to understand rules and build abstractions by integrating relationships based on non-social visual information.…”
Section: Discussionmentioning
confidence: 53%
“…11 The correlation between neurocognitive function and RMET was also observed in recent studies involving various clinically-ill patients groups, such as Autism spectrum disorder, 11 Attention deficit hyperactivity disorder, 21 and dementia. 22 Reasoning by analogy is the ability to understand rules and build abstractions by integrating relationships based on non-social visual information. According to the developers of the RMET, 4 when RMET subjects match the descriptors regarding the complex mental state to corresponding part of facial expressions (i.e., the eye region of face), they should map the eyes in each photograph to examples of eye regions from their memory.…”
Section: Discussionmentioning
confidence: 99%
“…ToM refers to the ability of an individual to understand the mental states of oneself and others, and depends on executive functions and memory (Castelli et al, 2011). It was reported that 65% of AD dementia patients exhibited cognitive ToM deficits, and these deficits were associate with multiple domains of cognitive impairments (Yildirim et al, 2020). Similar to ACEIs, H3R antagonists are reported to have cognitive enhancing effects with positive results in memory and attention (Nathan et al, 2013), suggesting the important role of histamine in disorders associated with memory and cognitive impairments, and proposing the special role it might have in ToM.…”
Section: Common Neurotransmitter Changes In Asd Bpsd and Schmentioning
confidence: 99%